Influence of emotional intelligence on organizational performance among insurance companies in Kenya - Grace Wangari Mwangi; D. M. Gichuhi; S. M. Macharia (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: The purpose of this study was to establish the influence of emotional intelligence on organizational performance among insurance companies in Kenya. Design/methodology/approach: Positivism research philosophy was adopted for the study. Descriptive and explanatory cross-sectional research designs were used. The target population consisted of all the 55 registered insurance companies in Kenya as at 28th February 2017 and a sample size of 208 participants drawn from lower, middle and top level. Primary data was collected using collected using semi-structured questionnaires containing both open and closed-ended questions while secondary data was obtained using a secondary data collection sheet. Data analysis was conducted using descriptive statistics and inferential analysis. Findings: There is a weak positive correlation between self-awareness and organization performance. Self-management, social awareness, and organization performance were moderately correlated while interpersonal relationship management was strongly correlated with organization performance. Emotional intelligence has a significant influence on organizational performance among insurance companies in Kenya. Specifically, selfawareness, self-management, social awareness, and interpersonal relationship management have a significant impact on organizational performance among insurance companies in Kenya. Research limitations/implications: Study was limited in scope since it focused on the Kenyan insurance firms and thus the findings might not be generalized to other sectors such as banking and agricultural sectors. The management of insurance companies should ensure that they cultivate, create and maintain good rapport with stakeholders, seek to understand each stakeholder requirements, observe healthy competition with competitors, encourage amicable conflict resolution where grievances arise and enhance effective communication within and outside the organization. Insurance companies should ensure that there are programs that are specially designed to offer training and enhancement of self-awareness to help the management staff and employees to be emotionally stable and make optimal decisions. Originality/value: The results of this research will add knowledge in the available literature on emotional intelligence and how it impacts on the performance of organizations by showing that emotional intelligence plays a significant role in personal career development and motivating people to act and control their actions and emotions.
Keywords: L60; M12; M16; 330; Emotional Intelligence; Organizational Performance; Insurance companies